INOVASI TEKNOLOGI PEMBELAJARAN MATEMATIKA DIANTARA DESAKAN ERA SOCIETY 5.0 DI KOTA PONTIANAK - Kintan Salsabila Hasria Syafitri; Ahmad Yani T.; Nurfadilah Siregar (Universitas Bhinneka PGRI, 2025)
Innovation in mathematics learning technology is a signal in the Society 5.0 era and should ideally be reflected in mathematics education, including in schools in the Pontianak City area. This research aims to analyze the innovation of mathematics learning technology in accordance with the demands of the Society 5.0 era. The research method uses a qualitative-exploratory approach. The research results show that there is still a gap between the dynamic development of technology and teachers' ability to incorporate technology into their teaching. This gap occurs due to teachers' tendency to prioritize lecture methods, note-taking, and conventional problem-solving exercises. As a result, the innovation of technology in mathematics learning has not been well implemented. In fact, the sophistication of technology through Artificial Intelligence (AI), Big Data, and the Internet of Things (IoT) promises effectiveness and efficiency in learning. That reality serves as a sign that teachers involved in mathematics education need to be motivated and their awareness of innovative capabilities needs to be enhanced, so that the mathematics teaching methods implemented become more modern. Maximizing the potential of technology in accordance with the demands of the current era. Supporting a more adaptive and interactive curriculum. Students can be more active and critical, and can interpret and apply mathematical knowledge in everyday life.